Proton and light ion RBE for the induction of direct DNA double strand breaks. Issue 5 (5th April 2016) - Pater, Piotr; Bäckstöm, Gloria; Villegas, Fernanda; Ahnesjö, Anders; Enger, Shirin A.; Seuntjens, Jan; El Naqa, Issam
Abstract : Purpose: To present and characterize a Monte Carlo (MC) tool for the simulation of the relative biological effectiveness for the induction of direct DNA double strand breaks ( RBE DSB direct ) for protons and light ions. Methods: The MC tool uses a pregenerated event‐by‐event tracks library of protons and light ions that are overlaid on a cell nucleus model. The cell nucleus model is a cylindrical arrangement of nucleosome structures consisting of 198 DNA base pairs. An algorithm relying on k ‐dimensional trees and cylindrical symmetries is used to search coincidences of energy deposition sites with volumes corresponding to the sugar–phosphate backbone of the DNA molecule. Strand breaks (SBs) are scored when energy higher than a threshold is reached in these volumes. Based on the number of affected strands, they are categorized into either single strand break (SSB) or double strand break (DSB) lesions. The number of SBs composing each lesion (i.e., its size) is also recorded. RBE DSB direct is obtained by taking the ratio of DSB yields of a given radiation field to a 60 Co field. The MC tool was used to obtain SSB yields, DSB yields, and RBE DSB direct as a function of linear energy transfer (LET) for protons ( 1 H + ), 4 He 2+, 7 Li 3+, and 12 C 6+ ions. Results: For protons, the SSB yields decreased and the DSB yields increased with LET. At ≈24.5 keV μ m −1, protons generated 15% more DSBs than 12 C 6+ ions. The RBE DSB direct varied between 1.24 and 1.77 for proton fields between 8.5 and 30.2 keV μ m −1, and it was higher for iso‐LET ions with lowest atomic number. The SSB and DSB lesion sizes showed significant differences for all radiation fields. Generally, the yields of SSB lesions of sizes ≥2 and the yields of DSB lesions of sizes ≥3 increased with LET and increased for iso‐LET ions of lower atomic number. On the other hand, the ratios of SSB to DSB lesions of sizes 2–4 did not show variability with LET nor projectile atomic number, suggesting that these metrics are independent of the radiation quality. Finally, a variance of up to 8% in the DSB yields was observed as a function of the particle incidence angle on the cell nucleus. This simulation effect is due to the preferential alignment of ion tracks with the DNA nucleosomes at specific angles. Conclusions: The MC tool can predict SSB and DSB yields for light ions of various LET and estimate RBE DSB direct . In addition, it can calculate the frequencies of different DNA lesion sizes, which is of interest in the context of biologically relevant absolute dosimetry of particle beams.